Victorian Christianity at the fin de siècle: the culture of English religion in a decadent age - Knight, Frances (Library of modern religion, 2016)
The period known as the fin de siècle (usually taken to mean the years between 1870 and 1914) was a fluid and unsettling epoch of endings and beginnings, as well as of new forms of creativity and anxiety. The end of the century has attracted much interest from scholars of literary and cultural studies, who regard it as a critical moment in the history of their disciplines; but it has been almost completely ignored by religious historians. Frances Knight here sets right that neglect. She shows how late Victorian Britain (often said to be one of the most intensely Christian societies the world has ever seen) reacted to the bold agendas being set by the thinkers of the fin de siècle; and how prominent Church figures during the era first identified many of the concerns that have preoccupied Christians latterly. These include a nascent interest in social justice and alleviating poverty; the rise of liberalism and debates about societys decadence ; new ideas about the role of women; and the increasing sophistication of biblical and archaeological scholarship from pioneering figures like J B Lightfoot, Francis Crawford Burkitt and Flinders Petrie